The Frequency of Mediastinal Lymph Node Calcification in Sarcoidosis Patients and the Influencing Factors - Pelin Pınar Deniz; Pelin Duru Çetinkaya; Saida Mehdiyeva; İsmail Hanta (Medicina)
Background and Objectives: This study investigates the prevalence of calcification in mediastinal lymph nodes among sarcoidosis patients and the influencing factors. Sarcoidosis is a multisystemic inflammatory disease characterized by non-caseating epithelioid granulomas. Bilateral hilar lymphadenopathy (LAP) is the most common radiographic finding, with studies showing a correlation between the frequency of lymph node calcification and disease duration, with a frequency of 3% relating to a duration of 5 years and a frequency of 20% relating to one of 10 years. Materials and Methods: This study involved fifty-seven patients diagnosed with sarcoidosis at our chest disease outpatient clinic from January 2020 to September 2022. We examined patient records to determine demographics, radiological findings, and respiratory function parameters. Results: The mean age of patients was 55.07 ± 13.53 (21–90). We identified eighty percent of patients with stage 2 sarcoidosis. Hilar lymph node calcification was observed in 13 cases (22.8%). Among the 13 cases, punctate calcification was detected in 2 (15.4%), while diffuse calcification was observed in 11 (84.6%). The mean duration of sarcoidosis diagnosis in patients was 4.1 ± 3.2 years (range: 1–14 years). Within the first 5 years after diagnosis, calcification in lymph nodes was detected in 18.6% of cases, while of patients diagnosed more than 5 years ago, 35.71% showed lymph node calcification. Conclusions: Our findings suggest that mediastinal lymph node calcification is more common than previously reported, and integrating clinical evaluation and patient history in cases with bilateral hilar LAP can help to avoid unnecessary invasive and costly procedures.